Bacteriological Quality of Foods for Sale in the Traditional Market - Amyati Amyati; Nor Wijayanti (LPPM STIKES KENDAL, 2020)
Food is the number one physiological need for humans so these needs must be met so that it does not have a negative impact on health. Health relationship with food is very close. One way to maintain food is by sanitation. Sanitation is an important part in the processing of food consumed. Bacterial contaminated food can cause health problems if consumed by the public. These health problems include food poisoning, diarrhea, gastroenteritis, and other digestive disorders, which can even cause death if bacterial contamination is very high. The purpose of this study was to determine the quality of the bacteria Eshericia coli, Staphylococus Aureus and Salmonella Thypi in food sold at the Beringharjo Market in Yogyakarta. This type of research used in this research is quantitative descriptive with experimental methods. This research examines food sold in the Beringharjo Market in Yogyakarta. The sampling technique uses purposive sampling. The sample used was 15 types of food sold in the Beringharjo market. Data analysis using laboratory tests. Laboratory test results related to E. Colli bacteria on 15 food samples sold in Yogyakarta Beringharjo Market showed positive results on 3 types of food and negative or 0 gr / colony on 12 types of food. While laboratory tests on the content of the bacteria Staphylococcus aureus and Salmonella Thypi on 15 food samples after laboratory testing showed that the results were negative or not contaminated.